Report on the geological survey in the Urubamba river inferior area of the Republic of Peru. Final Report - Japan International Cooperation Agency (1977)
This report describes results of the first year's survey in FY1998(Phase I) and the second year's survey in FY1999(Phase II), implemented in the Urubamba river inferior area of the Republic of Peru, under the technical cooperation for the mineral exploration. The survey was conducted with an aim to effectively select promising zones from the extensive survey arca in a short period of time, by means of satellite image analysis, existing data analysis and integrated studies of survey findings of an area upstream of the Amazon in eastern Peru, which covers the Ucayali River Basin and its upper streams, the Urubamba and the Tambo, where the metallogenic zoning has not been clarified in detail. The Urubamba river inferior arca covers an arca of about 65,500 km2, spreading over the 27 quadrangles of the 1:100,000-scale topographic map issued by the National Geographical Instituto of Peru. Topographically, the area extends from the Sub-Andes in the west to the Selva in the east. In Phase 1, the analysis of the JERS-1 SAR images was conducted of the 15 quadrangles (approx. 37,500km2; 72° 30' to 75° 00' W of longitude and 9° 30' S to 11° 00' S of latitude) west of the Urubamba inferior are a, while the analysis of existing Data was conducted of the whole inferior area of the Urubamba. Simultaneously, the technology transfer to the INGEMMMET, the Peruvian counterpart for the survey, was implemented concerning the methods of satellite image analysis. In Phase II, the analysis of the JERS-1 SAR images was conducted of the 12 quadrangles (approx. 28,000km2; 70° 30' to 72° 30' W of longitude and 9° 30' to 11° 00' S of latitude) west of the Urubamba inferior area. Resides, an integral analysis was conducted on the basis of the combined results of the satellite image analysis in Phases 1 and 11 and the analysis of the existing data, in order to evaluate potentials for occurrence of ore deposits in the entire inferior areas of the Urubamba River.